A történelmi magyar-román határszakasz felülvizsgálata 1941-ben - Suba, János (Közép-Európai Közlemények, 2016)
The territory and borders of Hungary changed in 1941. By annexing North Transylvania, Hungary regained its historical borders. A part of the „new” border was the same as the former one. In other words, the border had already been marked by border signs, only the coats of arms /armours/had to be changed. The historical borders underwent revisions in the years 1900 and 1910. As a result of the Peace Treaty of Trianon, this border ceased to be legal. It became legal again in 1941. As a consequence, it was necessary toguard and patrol the borders, in other words: checkf the border markers and survey points that had been placed previously. This paper is about the revision of the border, which was carried out unilaterally by Hungary. The execution was confidential. It was carried out by the officers of the Hungarian border troops. They went along the borderline in the Carpathian Mountains, reset the borderline and visited the old border markers after 27 years. They made arrangements for the designation of the borderline in the Carpathian Mountains.